Bamboo joints with steel clamps capable of transmitting moment. (20th August 2019) - Moran, Richard; García, José J.
Highlights: Three new bamboo moment connections based on steel clamps are proposed. Connections were evaluated under static monotonic and cyclic tests. Mechanical performance of prototypes was higher than that of conventional connections. Abstract: Bamboo has become a promising sustainable material for structural applications. The design of normalized efficient connections is one challenge that has to be solved to increase the use of raw bamboo in construction. Current bamboo connections are considered to be unable to transmit moment, limiting the use of the material in several applications. We propose three new beam-column bamboo connections capable of transmitting moment. Each joint is comprised of five thin steel clamps tightened around the culms, which are connected with small steel angles and platens in different configurations. Steel clamps provide great versatility and avoid premature failures. Static monotonic tests showed stiffness, strength and ductility in the ranges of 73.4–230.8 kN.m/rad, 3.4–5.2 kN.m and 3.6–17.2, respectively, for the three designs. Average stiffness and strength of these connections were at least 29% and 250% higher than those reported for conventional mortar-injected bolted connections. Cyclic tests of the connections showed hysteresis loops with pinched regions without strength degradation which is characteristic of timber connections. This study shows that clamp moment connections are a feasible alternative to improve the structural performance and versatility of bamboo structures.